Structure-Based Identification of Sanketan Heliotropium indicum as a RANK-RANKL Inhibitor: A Bioinformatics Approach for Osteoporosis Therapy - rizkita, aden; Sintia Ayu Dewi; Taufik Muhammad Fakih; Candra Hermawan; Vivi Amalia Dwi Pratiwi (Prodi Kimia, 2025)
Heliotropium indicum, a traditional medicinal plant, contains a variety of bioactive compounds with potential therapeutic effects. This study employed a structure-based virtual screening approach to evaluate the inhibitory potential of selected compounds from H. indicum against RANKL (Receptor Activator of Nuclear Factor κB Ligand), a key regulator in osteoclastogenesis and osteoporosis. Molecular docking simulations were performed using AutoDockTools integrated with PyRx, targeting the RANKL crystal structure (PDB ID: 3QBQ). The binding free energy (ΔG) values were used to assess ligand affinity, with Indicine (–5.6 kcal/mol), Heliotrine (–6.0 kcal/mol), and 24-Methylenecholesterol (–6.6 kcal/mol) demonstrating the strongest binding affinities. Interaction analyses revealed stable hydrogen bonding and hydrophobic contacts with key residues such as SER296, ARG222, and GLY96. Further ADME-Tox profiling and Lipinski’s Rule of Five filtration indicated that most compounds possess favorable pharmacokinetic properties, including high gastrointestinal absorption, non-substrate behavior toward P-glycoprotein, minimal CYP450 inhibition, and low toxicity risks. Notably, Indicine and Heliotrine exhibited superior drug-likeness and safety profiles, while 24-Methylenecholesterol also emerged as a promising lead despite slightly lower binding affinity. These findings suggest that specific bioactive constituents of H. indicum could serve as potential RANKL inhibitors for osteoporosis therapy. The combined computational evaluations provide a strong foundation for future in vitro and in vivo validation, supporting the development of novel phytopharmaceuticals targeting bone resorption pathways